Lucky you [videorecording (DVD)] - Hanson, Curtis; Bana, Eric; Barrymore, Drew; Duvall, Robert; Messing, Debra, 1968- (Distributed by Warner Home Video, 2007)
Pro gambler Huck Cheever meets irresistible Billie Offer. He learns to treat love the way he treats cards: trusting his heart instead of his head. Meanwhile, he scrambles to raise the $10K entry fee for the glittery, high-roller World Series of Poker, even though, or maybe because, the tournament may pit him against his estranged father.